2021
DOI: 10.1088/1742-6596/1879/2/022041
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of the effect of zinc oxide nanoparticles on Streptococcus mutans isolated from human dental caries

Abstract: Dental caries is a public health concern worldwide for which Streptococcus mutans has been reported Known as the potential etiology of infection. In recent years, nanotechnology has applied to Creation of novel material properties. The research was studying the effects of Nanoparticles of Zinc Oxide on Streptococcus mutans isolate from dental caries. In this research, Different ZnO NPs concentrations were studied as its anti-bacterial effects on Streptococcus mutans was isolated from dental caries cases. 27 St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…The antibacterial activities of Zn NPs were investigated by determining the lowest inhibitory concentration against E.coli bacteria, which was corroborated by (26). Diffusion in the pits was used to monitor the antibacterial nanoparticle's quantitative assessment, and it was shown that the area of inhibition mostly relied on the concentration and agreement with results by the (14). It showed that bacterial inhibition increased as ZnO NP concentration was raised.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The antibacterial activities of Zn NPs were investigated by determining the lowest inhibitory concentration against E.coli bacteria, which was corroborated by (26). Diffusion in the pits was used to monitor the antibacterial nanoparticle's quantitative assessment, and it was shown that the area of inhibition mostly relied on the concentration and agreement with results by the (14). It showed that bacterial inhibition increased as ZnO NP concentration was raised.…”
Section: Discussionmentioning
confidence: 75%
“…Then, 100 μl of each treatment were added to ZnO NPs and Bifidobacterium bifidum at a concentration of 2 mg/ml, and the plates were incubated at 37 °C for 24 hours. Next, the inhibition zone was evaluated 14 .…”
Section: In Vitro Assessment Of the Efficacy Of Znonps And Bifidobact...mentioning
confidence: 99%
“…Hasil ini sejalan dengan penelitian (Afrasiabi et al, 2020;Wassel & Khattab, 2017) yang menunjukan beberapa senyawa bahan alam seperti propolis dan siwak efektif menghambat pertumbuhan dan mengurangi biofilm yang dibentuk oleh bakteri S. Mutans. Selain dari bahan alam, logam nanopatikel seperti emas, perak dan seng juga memperlihatkan aktivitas yang sangat baik dalam menghambat pertumbuhan bakteri S. Mutans (Espinosa-Cristóbal et al, 2018;Hamad & Mahmood Atiyea, 2021;Sadony & Abozaid, 2020).…”
Section: Uji Aktivitas Antibakteriunclassified
“…Zinc oxide nanoparticles have better antimicrobial activity than other zinc nanoparticles [42,43]. In addition, zinc oxide nanoparticles inhibit growth of S. mutans [44]. The nanoparticles can be added to restorative materials to prevent caries.…”
Section: Zinc Nanoparticlesmentioning
confidence: 99%
“…• Inhibiting growth of S. mutans[44,[50][51][52], S. aureus[46], S. sobrinus[48], and oral biofilm[52];•Uncompromising mechanical properties[51,52] and bond strength[59].…”
mentioning
confidence: 99%